A computational method for evaluating the damage in a solder joint of an electronic package subjected to thermal loads. Issue 3 (2014) - Jonas Johansson; Ilja Belov; Erland Johnson; Peter Leisner
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to introduce a novel computational method to evaluate damage accumulation in a solder joint of an electronic package, when exposed to operating temperature environment. A procedure to implement the method is suggested, and a discussion of the method and its possible applications is provided in the paper. Design/methodology/approach – Methodologically, interpolated response surfaces based on specially designed finite element (FE) simulation runs, are employed to compute a damage metric at regular time intervals of an operating temperature profile. The developed method has been evaluated on a finite‐element model of a lead‐free PBGA256 package, and accumulated creep strain energy density has been chosen as damage metric. Findings – The method has proven to be two orders of magnitude more computationally efficient compared to FE simulation. A general agreement within 3 percent has been found between the results predicted with the new method, and FE simulations when tested on a number of temperature profiles from an avionic application. The solder joint temperature ranges between +25 and +75°C. Practical implications – The method can be implemented as part of reliability assessment of electronic packages in the design phase. Originality/value – The method enables increased accuracy in thermal fatigue life prediction of solder joints. Combined with other failure mechanisms, it may contribute to the accuracy of reliability assessment of electronic packages.